Is it Time to Develop Government Communication Functions? - Radwan, Ahmed Farouk (ALBAHITH ALALAMI, 2023)
Embracing digital technological advancements in media and communication has led government entities to adopt communication practices fully aligned with the digital and networked system in government communication. Traditional media practices within the government environment increasingly rely on the ability to utilize digital tools and systems for content creation, communication, evaluation, and the management of the entire communication process within an electronic and intelligent framework for government services. Naturally, this transformation has caught the attention of communication and public relations researchers worldwide, as the digital and networked aspects of government communication now form an intellectual and theoretical dimension that cannot be underestimated in studying government communication practices.